Bariatric surgery‐induced weight loss causes remission of food addiction in extreme obesity. (23rd May 2014) - Pepino, Marta Yanina; Stein, Richard I.; Eagon, J. Christopher; Klein, Samuel
<x xml:space="preserve">Abstract</x> Objective To test the hypotheses that bariatric surgery‐induced weight loss: 1 induces remission of food addiction (FA), and 2 normalizes other eating behaviors associated with FA. Methods Forty‐four obese subjects (BMI= 48 ± 8 kg/m2) were studied before and after ∼20% weight loss induced by bariatric surgery (25 Roux‐en‐Y gastric bypass, 11 laparoscopic adjustable gastric banding, and eight sleeve gastrectomy). We assessed: 1 FA (Yale Food Addiction Scale), 2 food cravings (Food Craving Inventory), and 3 restrictive, emotional and external eating behaviors (Dutch Eating Behavior Questionnaire). Results FA was identified in 32% of subjects before surgery. Compared with non‐FA subjects, those with FA craved foods more frequently, and had higher scores for emotional and external eating behaviors (all P‐values <0.01; all Cohen's d >0.8). Surgery‐induced weight loss resulted in remission of FA in 93% of FA subjects; no new cases of FA developed after surgery. Surgery‐induced weight loss decreased food cravings, and emotional and external eating behaviors in both groups (all P‐values < 0.001; all Cohen's d ≥ 0.8). Restrictive eating behavior did not change in non‐FA subjects but increased in FA subjects (P < 0.01; Cohen's d>1.1). Conclusion Bariatric surgery‐induced weight loss induces remission of FA and improves several eating behaviors that are associated with FA.